Inclusivity of virtual tourism destinations: An immersive netnographic study of Indonesian wheelchair users in virtual nature-based destinations - Rosliyana Perangin-Angin; Rokhshad Tavakoli; Camelia Kusumo; Paolo Mura (Annals of Tourism Research Empirical Insights, 2025)
Exclusion-inclusion theory has received attention in various disciplines in the actual world. However, whether and how virtual tourism experiences can affect the degree of exclusion-inclusion for people who use wheelchairs has not been discussed. Driven by an interpretivist paradigm, this study employed immersive netnography. Ten Indonesian were observed and interviewed to understand their virtual nature-based experiences. They used virtual reality head month and explored a few virtual destinations. The findings suggest that the combination of virtual tourism destinations' aspects can influence the inclusivity of their travel experiences. A better understanding of these findings will aid in developing inclusive tourism for wheelchair users through virtual tourism. This paper provides insights into the current and future scope of inclusive e-tourism.
Keywords: 330; Exclusion-inclusion theory; Immersive Netnography; Inclusive e-tourism; Person who uses a wheelchair; Virtual tourist behaviour